Large-scale hybrid silver nanowall-reduced graphene oxide biofilm: A novel morphology by facile electrochemical deposition - Rafieerad, Ali Reza; Bushroa, Abdul Razak; Amiri, Ahmad; Gopinath, Venkatraman; Sookhakian, Mehran; Baradaran, Saeid; Rafieerad, M.; Saber-Samandari, Saeed; Vadivelu, Jamuna (Elsevier, 2018)
Increased attention has been focused on development of large-surface-area nanoengineered materials to enhance bone implants performance. Appropriate incorporations of functionalized carbon-based biofilms on the surface of artificial bone tissues can provide improved mechanobiological features. Besides, well-adhered potential coating interfaces corresponding wide spectrum antibacterial targets. Here, a novel morphology of hybrid silver (Ag) nanowall-green reduced graphene oxide (rGO) via facile methodology modified as-sputtered Ag grains to support Ti6Al7Nb implant (Ti67IMP) alloy. Layer-by-layer inorganic-organic topography obtained by physical vapor deposition magnetron sputtering (PVDMS) and subsequent one-step electrochemical deposition (ED) protocols. Microstructure, mechanical and wettability properties were characterized and cytocompatibility of designed composite-Ti67IMP system with human MG-63 osteosarcoma confirmed.